Method for protecting indium-indium oxide heterojunction electrocatalyst
By depositing a nitrogen-doped carbon layer on the surface of indium oxide nanospheres and forming a nitrogen-doped carbon-coated indium-indium oxide heterojunction catalyst, the problem that indium oxide is easily reduced completely under CO2 reduction potential is solved, and efficient CO2 electrocatalytic activity and selectivity are achieved.
Patent Information
- Application Number
- CN202510290806.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-05-30
- Estimated Expiration
- 2045-03-12
AI Technical Summary
In the prior art, indium oxide is easily reduced to metal indium under CO2 reduction potential, resulting in unstable metal-metal oxide heterostructure, a decrease in the number of active sites, and a decrease in CO2 electrocatalytic activity and selectivity.
A nitrogen-doped carbon layer was deposited on the surface of indium oxide nanospheres by chemical vapor deposition, and a nitrogen-doped carbon-coated indium-indium oxide heterojunction electrocatalyst was formed through electrochemical in situ reduction technology, which limited electron transport through Schottky barrier to achieve self-limiting reduction.
It effectively protects the In-In2O3 heterostructure, maintains the stability of the active site, and significantly improves the electrocatalytic activity and selectivity of CO2.
Smart Images

Figure CN120072959A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalytic reduction of CO 2 and specifically relates to a method for protecting indium - indium oxide heterojunction electrocatalysts. Background Art
[0002] Disclosing the information of this background art section is only intended to increase some understanding of the overall background of the present invention, and it is not necessarily regarded as an admission or an implication in any form that this information constitutes the prior art already known to those of ordinary skill in the art.
[0003] Driven by the accelerating global industrialization process and the continuous growth of the population, the excessive consumption of fossil fuels has led to a sharp rise in the atmospheric carbon dioxide concentration, exacerbating environmental crises such as the greenhouse effect and climate change. In this context, the electrocatalytic carbon dioxide reduction technology (CO2RR) has attracted much attention due to its dual benefits of converting CO 2 into high - value - added carbon - based fuels (such as formic acid, ethylene and other C1 - C2 compounds) under mild conditions. Therefore, designing highly active advanced electrocatalysts to achieve the efficient conversion and utilization of CO 2 is extremely urgent.
[0004] p - block metal indium has the characteristics of low toxicity and environmental friendliness. Its unique oxygen - loving property, which tends to adsorb formic acid intermediates, is considered to be one of the most potential catalysts for electrocatalytic synthesis of formic acid from CO 2 Generally speaking, its excellent activity is mainly attributed to the heterostructure formed by the metal and its oxidation state, which can effectively inhibit the hydrogen evolution reaction and reduce the CO 2 activation energy. However, metal oxides will undergo self - reduction during the electro - reduction process and all turn into metal sites, unable to maintain the stable existence of the metal - metal oxide heterostructure, resulting in a reduction in the number of active sites at the heterointerface and a decrease in catalytic activity and product selectivity. Summary of the Invention
[0005] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide a method for protecting indium - indium oxide heterojunction electrocatalysts, which combines chemical vapor deposition and in - situ electrochemical reduction technology to solve the problem that indium oxide is easily completely reduced to metallic indium at the CO 2 reduction potential, the instability of the metal - metal oxide heterostructure, the reduction in the number of active sites at the heterointerface, and the decrease in the electrocatalytic activity and selectivity of CO 2
[0006] The technical solution adopted by the present invention is as follows: First of all, the present invention discloses a method for protecting indium - indium oxide heterojunction electrocatalysts, including the following steps: (1) Indium nitrate, citric acid, and urea were successively dissolved in deionized water and stirred evenly until a colorless and transparent solution was formed. It was transferred to a reaction kettle for hydrothermal reaction. After natural cooling, it was centrifuged, washed, and dried to obtain indium hydroxide nanospheres, which were placed in a muffle furnace and calcined at high temperature to obtain indium oxide nanospheres; (2) Using chemical vapor deposition method, melamine and indium oxide nanospheres were placed at the upstream and downstream positions in a nitrogen atmosphere tubular furnace respectively. During the high-temperature calcination process, melamine was converted into nitrogen-doped carbon and in-situ deposited on the surface of indium oxide nanospheres, thus obtaining indium oxide nanospheres coated with nitrogen-doped carbon; (3) Using the in-situ electrochemical reduction technique, indium oxide nanospheres coated with nitrogen-doped carbon were dispersed in a water-ethanol mixed solution, and a Nafion binder was added and mixed to obtain an electrode paste. It was coated on the surface of carbon paper as a cathode electrode. In a three-electrode system, the indium oxide nanospheres electrode sheet coated with nitrogen-doped carbon was subjected to in-situ electrochemical reduction treatment using chronopotentiometry to obtain a nitrogen-doped carbon-coated indium-indium oxide heterojunction electrocatalyst.
[0007] Further, in step (1), the mass ratio of indium nitrate to citric acid is 1:2; the mass ratio of indium nitrate to urea is 1:2.5.
[0008] Further, in step (1), the hydrothermal reaction temperature is 140 °C and the reaction time is 12 h.
[0009] Further, in step (1), the washing refers to washing successively with water and ethanol respectively.
[0010] Further, in step (1), the drying temperature is 60 - 80 °C and the drying time is 8 - 12 h.
[0011] Further, in step (1), the calcination temperature in the muffle furnace is 500 °C and the time is 1 h.
[0012] Further, in step (2), the mass ratio of melamine to indium oxide nanospheres is 30~10:10~1, preferably 20:1.
[0013] Further, in step (2), the calcination temperature in the tubular furnace is 500 °C and the time is 1 - 3 h, preferably 2 h.
[0014] Further, in step (2) of the chemical vapor deposition method, during the high-temperature calcination process, the nitrogen atmosphere flow rate is 10~30 mL / min.
[0015] Further, in step (3), the volume ratio of water to ethanol in the water-ethanol mixed solution is 1:3, and the volume of the Nafion binder is 5~10% of the total volume of the water-ethanol mixed solution.
[0016] Furthermore, in step (3), the electrochemical reduction treatment adopts a three-electrode system, wherein the nitrogen-doped carbon-coated indium oxide nanosphere electrode material is the working electrode, silver / silver chloride is the reference electrode, and platinum sheet is the counter electrode. The in-situ electrochemical treatment is performed using an H-type electrolytic cell, and the cathode and anode chambers are separated by a Nafion 117 proton exchange membrane. The electrolyte in both chambers is 0.5 M potassium bicarbonate, and CO is continuously introduced into the cathode. 2 The current applied by chronopotentiometry was -10 to -50 mA cm -2 , time is 1 hour, and nitrogen-doped carbon-coated indium-indium oxide nanosphere heterojunction electrocatalyst is obtained.
[0017] In a second aspect of the present invention, a nitrogen-doped carbon-coated indium-indium oxide heterojunction electrocatalyst prepared by the above method is provided.
[0018] In a third aspect of the present invention, the nitrogen-doped carbon-coated indium-indium oxide heterojunction electrocatalyst is provided in CO 2 Application in catalytic reduction reactions.
[0019] Compared with the related art known to the inventor, one of the technical solutions of the present invention has the following beneficial effects: The present invention provides a method for protecting an indium-indium oxide heterojunction electrocatalyst. First, a nitrogen-doped carbon layer is deposited on the oxide surface by chemical vapor deposition. In a subsequent electrochemical in-situ reduction process, part of the In 2 O 3 When reduced to In elemental form, In and the nitrogen-doped carbon interface covering its surface form a Schottky barrier, actively restricting the electrons from moving to In. 2 O 3 The excessive transport of In and the self-limiting reduction is realized, and the in-situ formed In element interacts with the nitrogen-doped carbon layer to maintain the In-In 2 O 3 Dynamic equilibrium of heterojunction, stabilizing CO 2 Active sites for electrocatalytic reactions, achieving excellent electrocatalytic activity and selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.
[0021] Figure 1 In prepared in Example 1 of the present invention 2 O 3 Scanning electron microscope image.
[0022] Figure 2 NC@In prepared in Example 2 of the present invention 2O 3 -L SEM image.
[0023] Figure 3 NC@In prepared in Example 3 of the present invention 2 O 3 -M SEM image.
[0024] Figure 4 NC@In prepared in Example 4 of the present invention 2 O 3 -H SEM image.
[0025] Figure 5 In prepared in Examples 1 and 3 of the present invention respectively 2 O 3 and NC@In 2 O 3 -M X-ray diffraction pattern.
[0026] Figure 6 In and NC@In-In prepared in Examples 5 and 7 of the present invention respectively 2 O 3 -M X-ray diffraction pattern.
[0027] Figure 7 In and NC@In-In prepared in Examples 5 and 7 of the present invention respectively 2 O 3 -M in N 2 and CO 2 Linear sweep voltammetry curves in saturated electrolyte.
[0028] Figure 8 Products (a) In, (b) NC@In-In 2 O 3 -L, (c) NC@In-In 2 O 3 -M and (d) NC@In-In 2 O 3 -H Faraday efficiency diagrams of the products. Detailed Description of the Invention
[0029] It should be noted that the following detailed description is exemplary and is intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which the present invention belongs.
[0030] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they specify the presence of features, steps, operations, and / or combinations thereof.
[0031] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0032] Example 1: (1) Dissolve 1.5 g of In(NO 3 ) 3 ·4.5H 2 O (converted to 4 mmol) in 50 mL of H 2 O, then weigh 3.0 g (converted to 15 mmol) of citric acid and add it to the above solution, and stir for 10 min. Subsequently, weigh 3.75 g of urea (converted to 62.5 mmol) and add it to the above homogeneous solution, and continue to stir until a colorless transparent solution is formed.
[0033] (2) Transfer the mixed solution to a 100 mL autoclave, react at 140 °C for 12 h, and after naturally cooling to room temperature, wash the obtained product with ethanol and deionized water multiple times, and dry it overnight at 80 °C to obtain a precursor white precipitate.
[0034] (3) Transfer the precursor white precipitate to a muffle furnace, calcine it at 500 °C for 1 h in air at a heating rate of 4 °C / min, and obtain In 2 O 3 nanosphere material after natural cooling.
[0035] The material finally obtained in Example 1 is labeled as "In 2 O 3 ".
[0036] Example 2: Transfer 300 mg of melamine and 30 mg of In 2 O 3 obtained in Example 1 to a tubular furnace and place them upstream and downstream of the N 2 gas flow direction respectively. Using chemical vapor deposition method, calcine at 500 °C for 1 h under a protective atmosphere of N 2 , where the N 2 gas flow rate is 15 mL / min, and nitrogen-doped carbon-coated In 2 O 3Nanosphere material.
[0037] The material finally obtained in Example 2 was labeled "NC@In 2 O 3 -L".
[0038] Example 3: Transfer 600 mg of melamine and 30 mg of the In 2 O 3 nanosphere material in Example 1 to a tube furnace and place them respectively upstream and downstream of the N 2 gas flow direction. Using chemical vapor deposition method, calcine at 500 °C for 1 h under N 2 protective atmosphere, where the N 2 gas flow rate is 15 mL / min. After calcination, a nitrogen-doped carbon-coated In 2 O 3 nanosphere material is obtained.
[0039] The material finally obtained in Example 3 was labeled "NC@In 2 O 3 -M".
[0040] Example 4: Transfer 900 mg of melamine and 30 mg of the In 2 O 3 nanosphere material in Example 1 to a tube furnace and place them respectively upstream and downstream of the N 2 gas flow direction. Using chemical vapor deposition method, calcine at 500 °C for 1 h under N 2 protective atmosphere, where the N 2 gas flow rate is 15 mL / min. After calcination, a nitrogen-doped carbon-coated In 2 O 3 nanosphere material is obtained.
[0041] The material finally obtained in Example 4 was labeled "NC@In 2 O 3 -H".
[0042] Example 5: Using the material In 2 O 3 prepared in Example 1 above as a catalyst, disperse it in a water-ethanol (v / v = 1 / 3) mixed solution, then add 5% nafion conductive binder, ultrasonically mix evenly to obtain a catalyst ink, coat it on the surface of carbon paper as a working electrode, use a platinum sheet as a counter electrode, and an Ag / AgCl electrode as a reference electrode. Using chronopotentiometry in CO 2 continuously aerated 0.5 M KHCO 3Electrochemically treat the working electrode in the electrolyte at a current density of -25 mA cm -2 for 1 h to obtain an indium catalyst.
[0043] The material finally obtained in Example 5 is labeled "In".
[0044] Example 6: Use the material prepared in Example 2 above as a catalyst, disperse it in a water-ethanol (v / v = 1 / 3) mixed solution, then add 5% nafion conductive binder, and ultrasonically mix evenly to obtain a catalyst ink. Coat it on the surface of carbon paper as the working electrode, use a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode. Use chronopotentiometry in a 0.5 M KHCO 2 electrolyte with continuous ventilation to electrochemically treat the working electrode at a current density of -25 mA cm 3 for 1 h to obtain a nitrogen-doped carbon-coated indium-indium oxide heterojunction electrocatalyst. -2 The material finally obtained in Example 6 is labeled "NC@In-In
[0045] O 2 O 3 -L".
[0046] Example 7: Use the material prepared in Example 3 above as a catalyst, disperse it in a water-ethanol (v / v = 1 / 3) mixed solution, then add 5% nafion conductive binder, and ultrasonically mix evenly to obtain a catalyst ink. Coat it on the surface of carbon paper as the working electrode, use a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode. Use chronopotentiometry in a 0.5 M KHCO 2 electrolyte with continuous ventilation to electrochemically treat the working electrode at a current density of -25 mA cm 3 for 1 h to obtain a nitrogen-doped carbon-coated indium-indium oxide heterojunction electrocatalyst. -2 The material finally obtained in Example 7 is labeled "NC@In-In
[0047] O 2 O 3 -M".
[0048] Example 8: Use the material prepared in Example 4 above as a catalyst, disperse it in a water-ethanol (v / v = 1 / 3) mixed solution, then add 5% nafion conductive binder, and ultrasonically mix evenly to obtain a catalyst ink. Coat it on the surface of carbon paper as the working electrode, use a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode. Use chronopotentiometry in a CO 20.5 M KHCO for continuous ventilation 3 The working electrode was electrochemically treated in the electrolyte, and reacted at a current density of -25 mA cm -2 for 1 h to obtain a nitrogen-doped carbon-coated indium-indium oxide heterojunction electrocatalyst.
[0049] The material finally obtained in Example 8 was labeled "NC@In-In 2 O 3 -H".
[0050] The sample materials prepared in the above examples were characterized as follows: Product detection: The gas products after CO 2 electroreduction were on-line detected using a gas chromatograph. The reacted gas was introduced into the gas chromatograph for qualitative and quantitative analysis every 20 minutes. The reacted KHCO 3 electrolyte was analyzed using a nuclear magnetic resonance spectrometer. 0.5 mL of the reacted electrolyte was mixed with 0.1 mL of deuterium oxide, and 100 μL of dimethyl sulfoxide with a concentration of 6 mmol / L was added as an internal standard, and measured by the press water peak method.
[0051] Characterization results: It can be seen from the scan of Example 1 Figure 1 that the prepared indium oxide nanospheres have uniform morphology and complete structure. Its surface is composed of fine particles, and the diameter of the nanospheres is about 550 nm. As Figure 2 shown, using the chemical vapor deposition method, the precursor melamine polycondenses and transforms into nitrogen-doped carbon during high-temperature calcination, migrates to the surface of the nanospheres with the gas flow, and in-situ recrystallizes to form a nitrogen-doped carbon-coated indium oxide nanosphere structure, and the original fine and uniform particles on its surface transform into irregular particle coatings. With the increase of the amount of melamine, the nitrogen-doped carbon particles on the surface of the nanospheres melt and grow to form a uniform and flat covering layer ( Figure 3 ). When the amount of melamine continues to increase, the nitrogen-doped carbon layer coated on the indium oxide further thickens ( Figure 4 ), and due to the stress effect, it is extruded and broken. The thickness of the nanolayer is about 20 nm, and its fragmented structure will affect the performance of the subsequent CO 2 electrocatalytic reduction reaction.
[0052] As Figure 5 shown, In 2 O 3 and NC@ In 2 O 3 -M have similar diffraction patterns. The strong diffraction peaks appearing at 30.5°, 35.4°, 45. 6°, 51.0°, 60.6°, etc. are mainly attributed to In 2O 3 (JCPDS 06-0416). However, compared with the diffraction peaks of In 2 O 3 , no obvious diffraction peaks of nitrogen-doped carbon were found in NC@In 2 O 3 -M, which may be due to the small amount of nitrogen-doped carbon. As Figure 6 shown, after the electrochemical in-situ reduction reaction of NC@In 2 O 3 -M, strong diffraction peaks appear near 32.9°, 36.3°, and 39.1°, which belong to elemental In (JCPDS 05-0642). This is because most of In 2 O 3 is reduced to metallic In at negative potentials. However, weak diffraction peaks of In 2 O 3 can still be observed in the spectrum. This is because when part of In 2 O 3 is reduced to In elemental, a Schottky barrier is formed at the interface between In and nitrogen-doped carbon, hindering the further transmission of electrons into In 2 O 3 , causing the reduction reaction to spontaneously terminate after a certain amount of In is formed, thereby protecting the In 2 O 3 active species and maintaining the coexistence structure of In-In 2 O 3 , and finally obtaining the NC@In-In 2 O 3 -M heterojunction electrocatalyst. For In 2 O 3 without the protection of nitrogen-doped carbon, after the CO 2 electroreduction reaction, all the oxidation peaks in the spectrum disappear and are all reduced to metallic In elemental, indicating the key role of the nitrogen-doped carbon layer in protecting the indium-indium oxide heterostructure.
[0053] Using NC@In-In 2 O 3 -M and In as the working electrodes respectively, linear sweep voltammetry tests were carried out in 0.5 M KHCO 2 saturated with N 2 and CO 3 solutions respectively. As Figure 7 shown, the current densities of the two samples in the CO 2 saturated electrolyte are higher than those in N 2 , indicating that they have obvious catalytic activity for CO 2 reduction. Among them, NC@In-In 2 O3 -M shows a larger current density. When the applied voltage reaches -1.2 V, the current density reaches 23 mA cm -2 , indicating its higher electrocatalytic activity. Subsequently, different thicknesses of nitrogen-doped carbon layers were deposited on the surface of In 2 O 3 to obtain NC@In-In 2 O 3 -L, NC@In-In 2 O 3 -M, NC@In-In 2 O 3 -H and In were subjected to constant potential electrolysis tests. As 2 shown, the main product of CO Figure 8 electroreduction is HCOOH, and as the applied voltage increases, the Faraday efficiency of formic acid at the electrode gradually increases. Among them, NC@In-In 2 O 2 -M has the largest increase, reaching a maximum of 91.2% at -1.1 V, and the Faraday efficiency of C1 products is as high as 95.4%. The maximum Faraday efficiency of formic acid for In is only 88%, and the C1 products are also less than 90%. In addition, the maximum Faraday efficiencies of formic acid for NC@In-In 3 O 2 -L and NC@In-In 3 O 2 -H are 88.8% and 86.5% respectively, and the maximum Faraday efficiencies of C1 products are 91.7% and 90.7% respectively, all indicating that NC@In-In 3 O 2 -M has excellent electrocatalytic activity for CO 3 electroreduction. When the nitrogen-doped carbon layer deposited on the surface of In-In 2 O 2 is thin, it is difficult to form an effective Schottky barrier between In and the nitrogen-doped carbon, and a large number of electrons are transferred to the surface of the oxygen species and reduced, affecting the In-In 3 heterointerface, resulting in a small number of active sites and a decrease in electrocatalytic performance. When the nitrogen-doped carbon layer deposited on the surface of In-In 2 O 3 is thick, CO 2 molecules are difficult to be effectively adsorbed at the In-In 3 heterointerface and cannot be fully activated. At the same time, the thick outer shell ruptures under stress, exposing more In 2 O 2 O 3 heterointerface, and the oxygen species cannot be effectively protected. In, In 2 O 3 2 O 3 The heterogeneous interface is damaged, resulting in CO 2 The electrochemical performance is further reduced. NC@In-In 2 O 3 -M has significantly lower CO and H 2 Faradaic efficiencies than other electrodes, further confirming the excellent electrocatalytic product selectivity of NC@In-In 2 O 3 -M. In summary, the excellent performance of NC@In-In 2 O 3 -M is attributed to the fact that the nitrogen-doped carbon layer can effectively protect the In-In 2 O 3 heterostructure. The Schottky barrier formed between In and the nitrogen-doped carbon actively restricts the excessive transfer of electrons to In 2 O 3 to achieve self-limiting reduction, prevent it from being completely reduced to metallic indium during the CO 2 electroreduction process. The oxidation species present on the surface form a heterogeneous structure with metallic indium, providing abundant active sites for the reaction and simultaneously inhibiting the occurrence of the hydrogen evolution reaction, thus exhibiting excellent electrocatalytic activity and product selectivity.
[0054] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited by the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement methods and are all included in the protection scope of the present invention.
Claims
1. A method for protecting an indium-indium oxide heterojunction electrocatalyst, characterized in that: The following steps are involved: (1) Dissolving indium nitrate, citric acid and urea in deionized water successively, stirring evenly until a colorless transparent solution is formed, transferring the solution to a reactor for hydrothermal reaction, cooling naturally, centrifuging, washing and drying to obtain indium hydroxide nanospheres, placing the nanospheres in a muffle furnace, and calcining at high temperature to obtain indium oxide nanospheres; (2) placing melamine and indium oxide nanospheres at upstream and downstream positions in a nitrogen atmosphere tubular furnace, respectively. During high-temperature calcination, melamine is converted into nitrogen-doped carbon and in-situ deposited on the surface of the indium oxide nanospheres, thereby obtaining nitrogen-doped carbon-coated indium oxide nanospheres; (3) Dispersing nitrogen-doped carbon-coated indium oxide nanospheres in a water-ethanol mixed solution, adding Nafion binder to the mixture to obtain an electrode slurry, which was coated on the surface of carbon paper as a cathode electrode. In a three-electrode system, the nitrogen-doped carbon-coated indium oxide nanosphere electrode sheet was electrochemically reduced by chronopotentiometry to obtain a nitrogen-doped carbon-protected indium-indium oxide heterojunction electrocatalyst.
2. The method for protecting indium-indium oxide heterojunction electrocatalyst with carbon nitride as claimed in claim 1, characterized in that: In step (1), the mass ratio of indium nitrate to citric acid is 1:2; the mass ratio of indium nitrate to urea is 1:2.
5.
3. The method for protecting indium-indium oxide heterojunction electrocatalyst with carbon nitride according to claim 1, characterized in that: In step (1), the hydrothermal reaction temperature is 140° C. and the reaction time is 12 h.
4. The method for protecting indium-indium oxide heterojunction electrocatalyst with carbon nitride as claimed in claim 1, characterized in that: In step (1), the drying temperature is 60-80°C and the drying time is 8-12h; In step (1), the muffle furnace calcination temperature is 500° C. and the calcination time is 1 h.
5. The method for protecting indium-indium oxide heterojunction electrocatalyst with carbon nitride as claimed in claim 1, characterized in that: In step (2), the mass ratio of melamine to indium oxide nanospheres is 30-10:10-1, preferably 20:
1.
6. The method for protecting indium-indium oxide heterojunction electrocatalyst with carbon nitride as claimed in claim 1, characterized in that: In step (2), the calcination temperature in the tubular furnace is 500°C and the calcination time is 1 to 3 hours; In the vapor deposition method of step (2), during the high-temperature calcination process, the flow rate of the nitrogen atmosphere is 10-30 mL / min.
7. The method for protecting indium-indium oxide heterojunction electrocatalyst with carbon nitride as claimed in claim 1, characterized in that: In step (3), the volume ratio of water to ethanol in the water-ethanol mixed solution is 1:3, and the volume of the Nafion binder is 5-10% of the total volume of the water-ethanol mixed solution.
8. The method for protecting indium-indium oxide heterojunction electrocatalyst with carbon nitride as claimed in claim 1, characterized in that: Step (3) The electrochemical reduction treatment adopts a three-electrode system, with nitrogen-doped carbon-coated indium oxide nanosphere electrode material as the working electrode, silver / silver chloride as the reference electrode, and platinum sheet as the counter electrode. The electrochemical treatment is carried out using an H-type electrolytic cell, and the cathode and anode chambers are separated by a Nafion 117 proton exchange membrane. The electrolyte in both chambers is 0.5 M potassium bicarbonate, and CO2 is continuously introduced into the cathode. The current applied by the chronopotentiometry is -10~-50 mA cm -2 , time is 1 hour, and nitrogen-doped carbon-coated indium-indium oxide nanosphere heterojunction electrocatalyst is obtained.
9. The nitrogen-doped carbon-coated indium-indium oxide heterojunction electrocatalyst prepared by the method according to any one of claims 1 to 8.
10. Use of the nitrogen-doped carbon-coated indium-indium oxide heterojunction electrocatalyst according to claim 9 in catalytic CO2 reduction.
Citation Information
Patent Citations
Method for synthesizing carbon-coated indium oxide hollow rods
CN108793228A
Nitrogen-doped carbon supported tin and tin oxide nano composite material as well as preparation and application thereof
CN110743594A
Indium-indium trioxide heterogeneous nano-material composite electrocatalyst as well as preparation method and application thereof
CN111632587A
Indium-based oxide catalyst, modified coating, modified diaphragm and lithium-sulfur battery
CN117619370A
Chlorine-doped indium oxide electrode and preparation method and application thereof
CN117845254A